2019
DOI: 10.1016/j.bpj.2019.01.013
|View full text |Cite
|
Sign up to set email alerts
|

The Phospholamban Pentamer Alters Function of the Sarcoplasmic Reticulum Calcium Pump SERCA

Abstract: The interaction of phospholamban (PLN) with the sarco-endoplasmic reticulum Ca 2þ -ATPase (SERCA) pump is a major regulatory axis in cardiac muscle contractility. The prevailing model involves reversible inhibition of SERCA by monomeric PLN and storage of PLN as an inactive pentamer. However, this paradigm has been challenged by studies demonstrating that PLN remains associated with SERCA and that the PLN pentamer is required for the regulation of cardiac contractility. We have previously used two-dimensional … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
79
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(82 citation statements)
references
References 66 publications
3
79
0
Order By: Relevance
“…If hexamer and greater order PLB oligomers are required to form calcium channels, what is the physiologic role of pentameric PLB; the oligomeric species with the greatest preponderance on gels and most studied? There are number of studies providing evidence that PLB pentamers regulate SERCA, including a crystal structure of SERCA interaction with PLB pentamer and a demonstration that SERCA Vmax is increased with a higher concentration of PLN pentamer (Reddy, Cornea et al 2003, Trieber, Douglas et al 2005, Stokes, Pomfret et al 2006, Glaves, Primeau et al 2019. The Young group proposes that the PLN pentamer sits at the calcium entry funnel of SERCA when bound and its basic residues may thus perturb the surrounding lipid bilayer, resulting in greater mobility of SERCA catalytic pumps and an increased turnover capacity (Glaves, Primeau et al 2019).…”
Section: Role Of Plb Pentamermentioning
confidence: 99%
See 1 more Smart Citation
“…If hexamer and greater order PLB oligomers are required to form calcium channels, what is the physiologic role of pentameric PLB; the oligomeric species with the greatest preponderance on gels and most studied? There are number of studies providing evidence that PLB pentamers regulate SERCA, including a crystal structure of SERCA interaction with PLB pentamer and a demonstration that SERCA Vmax is increased with a higher concentration of PLN pentamer (Reddy, Cornea et al 2003, Trieber, Douglas et al 2005, Stokes, Pomfret et al 2006, Glaves, Primeau et al 2019. The Young group proposes that the PLN pentamer sits at the calcium entry funnel of SERCA when bound and its basic residues may thus perturb the surrounding lipid bilayer, resulting in greater mobility of SERCA catalytic pumps and an increased turnover capacity (Glaves, Primeau et al 2019).…”
Section: Role Of Plb Pentamermentioning
confidence: 99%
“…There are number of studies providing evidence that PLB pentamers regulate SERCA, including a crystal structure of SERCA interaction with PLB pentamer and a demonstration that SERCA Vmax is increased with a higher concentration of PLN pentamer (Reddy, Cornea et al 2003, Trieber, Douglas et al 2005, Stokes, Pomfret et al 2006, Glaves, Primeau et al 2019. The Young group proposes that the PLN pentamer sits at the calcium entry funnel of SERCA when bound and its basic residues may thus perturb the surrounding lipid bilayer, resulting in greater mobility of SERCA catalytic pumps and an increased turnover capacity (Glaves, Primeau et al 2019). Evidence suggesting functions of the PLB pentamer beyond direct regulation of SERCA have also been brought forth, such as its capacity to attenuate PKA to delay the phosphorylation of the PLB monomer (Wittmann, Lohse et al 2015).…”
Section: Role Of Plb Pentamermentioning
confidence: 99%
“…The effect of PLN on the apparent calcium affinity of SERCA saturates at a molar ratio of approximately one PLN monomer per SERCA (36,37) and it is assumed that SLN behaves in a similar manner. However, the PLN pentamer also affects the maximal activity of SERCA in a concentration dependent manner (11). This raises the question what are the consequences of higher ratios of SLN on SERCA maximal activity?…”
Section: Co-reconstitution Of Serca and Slnmentioning
confidence: 99%
“…We found that transmembrane segment M3 of SERCA formed a complementary hydrophobic interface with a SLN monomer. The interaction involved the opposite face of SLN's transmembrane helix (residues Leu 8 , Phe 12 of PLN and Glu 258 of SERCA (11). There is limited data on mutagenesis of these residues and the impact on SLN function, with the exceptions being Asn 4 -Ala (Figure 1) and Leu 8 -Ala (41).…”
Section: Molecular Model Of the Serca-sln Complexmentioning
confidence: 99%
See 1 more Smart Citation